Native pulmonary valve endocarditis requiring pulmonary valve replacement in adulthood: a case series. Issue 4 (18th April 2022) - Mohamed, S; Patel, A J; Mazhar, K; Osman, A; Balacumaraswami, L; Ridley, P
Abstract: Native pulmonary valve endocarditis is a rare phenomenon as native valve endocarditis tends to typically affect the left sided heart valves. However, the right-sided heart valves can be affected in patients with a history of intravenous drug use, whereby the tricuspid valve is most commonly affected. We present two cases who were diagnosed with native pulmonary valve endocarditis in the absence of congenital heart disease. In the first case, the native pulmonary valve endocarditis was probably a derivative of compounding factors of an enlarged underlying pulmonary artery and staphylococcal bacteraemia. In the second case, a common causal organism of native valve endocarditis following dental treatment and the resultant echocardiography findings was of significant interest. In summary, native pulmonary valve endocarditis is relatively rare complication in the adult population, especially in the absence of congenital heart disease.